Using Modeling and Simulation to Study Photon Number Splitting Attacks - Mailloux, Logan O.; Hodson, Douglas D.; Grimaila, Michael R.; Engle, Ryan D.; Mclaughlin, Colin V.; Baumgartner, Gerald B. (IEEE access, 2016)
Quantum key distribution (QKD) is an innovative technology, which exploits the laws of quantum mechanics to generate and distribute unconditionally secure shared cryptographic keying material between two geographically separated parties. The unique nature of QKD that ensures eavesdropping on the key distribution channel necessarily introduces detectable errors and shows promise for high-security environments, such as banking, government, and military. However, QKD systems are vulnerable to advanced theoretical and experimental attacks. In this paper, the photon number splitting (PNS) attack is studied in a specialized QKD modeling and simulation framework. First, a detailed treatment of the PNS attack is provided with emphasis on practical considerations, such as performance limitations and realistic sources of error. Second, ideal and non-ideal variations of the PNS attack are studied to measure the eavesdropper's information gain on the QKD-generated secret key bits and examine the detectability of PNS attacks with respect to both quantum bit error rate and the decoy state protocol. Finally, this paper provides a repeatable methodology for efficiently studying advanced attacks, both realized and notional, against QKD systems and more generally quantum communication protocols.